2021
DOI: 10.2991/assehr.k.211210.045
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio-Based Online Induction Model: Its Effect on Principal’s Instructional Leadership

Abstract: In the midst of the pressure COVID-19 pandemic in the digital era, the use of ICT has become a necessity. Therefore, it is necessary to develop a principal induction program that can be done online that can be accessed anytime and anywhere. This study aims to determine the effect of principals' portfolio-based online induction on principal's instructional leadership. This research was conducted with a quantitative approach. Data analysis was carried out, namely descriptive analysis and simple regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A principals cannot arbitrarily give orders to his subordinates. The principal as a direct leader is a real example in the work activities of his subordinates [26,27]. The results showed that the principals did not encounter serious problems related to ethical indicators in their social competence.…”
Section: Resultsmentioning
confidence: 99%
“…A principals cannot arbitrarily give orders to his subordinates. The principal as a direct leader is a real example in the work activities of his subordinates [26,27]. The results showed that the principals did not encounter serious problems related to ethical indicators in their social competence.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in the current digital era, as well as the pressure of the existing pandemic, without having qualified skills, of course the principal will not be able to lead the school properly [15,16]. The digital era, which is marked by the strong influence of ICT in the educational process, increasingly fierce competition and openness, brings its own challenges for school principals [17,18]. The principal has the responsibility to develop staff, curriculum, and the implementation of education in his school, in order to achieve quality in schools.…”
Section: Introductionmentioning
confidence: 99%